EDUCAÇÃO, CULTURA E HABITUS FRONTEIRIÇO NA MEMORIALÍSTICA DE HÉLIO SEREJO - Alice Felisberto da Silva (2017)
This research is linked to the Postgraduate Program in Education, Faculty of Education, Federal University of Mato Grosso do Sul, in the research line “School, Cultura and School Subjects. It seeks to understand the constitution of a frontier habitus. For this, an analysis of the memoirist Hélio Serejo’s work was made. The general objective of the research is to understand the constitution of a "frontier habitus" in the social, cultural, educational and religious practices, of the social groups that lived in the border in the period portrayed by the memorialist Hélio Serejo – late nineteenth and early twentieth century. To this end, the following specific objectives are established: 1) To extract from the Hélio Serejo’s work elements that reveal the educational process and the social, cultural, educational and religious practices of the frontier being (man / woman); 2) To characterize the way of life of these agents by configuring them as a social group with its singularities; and 3) To analyze if the singularity of the way of life of these groups constitutes a habitus of group, own of the Brazil-Paraguay border portrayed in the work of Hélio Serejo. The methodological course consists of a bibliographical review and the content analysis of the works of the memorialist. The theoretical perspective adopted is the theory of practice, developed by Pierre Bourdieu. It was possible to extract from the records of Serejo elements that reveal that the social practices at the frontier at that historical moment constituted a singular way of being, in the intense cultural exchanges developed there. It is observed that more studies are needed about other border contexts in order to elucidate how the border habitus manifests in these places, in different historical moments.